The Relationship Between Obstetric Factors and Postpartum Haemorrhage Maternal Deaths in Jember District - Gayatri, Mergy; Pratiwi, Dyah Krisnawati Satia; Pratiwi, Nanda Agnesia Jati; Sutrisno, Sutrisno; Arsana, I Wayan Agung (Green Publisher Indonesia, 2022)
Maternal mortality remains public health issue. One of its leading causes is postpartum haemorrhage. The aim of this study is to test the relationship between haemoglobin levels, perineal tear, retained placenta, uterine atony, and maternal mortality from postpartum haemorrhage in Jember district, Indonesia. This case-control study comprised 43 mothers died from postpartum haemorrhage (cases), and 43 mothers survived from postpartum haemorrhage (controls) between from January 2017 and December 2019. Data were obtained from maternal verbal autopsies, complemented by birth registrations and medical records in 26 community health centres across Jember district. The chi-square, and multivariate logistic regression were administered to test the hypothesis. The results of this study indicate that Haemoglobin levels (p = 0.032, OR 6.372, 95% CI 1.172 - 34.626), retained placenta (p = 0.033, OR 4.578 95% CI 1.128 – 18.587), and atonia utery (p= 0.014, OR 4.578 95% 1.364 – 16.502) had significant relationship with maternal deaths from postpartum haemorrhage. However, perineal tear (p= 0.155, OR 0.347 95% 0.081 – 1.490) had no significant relationship with maternal deaths from postpartum haemorrhage. The conclusion in this study is Identifying obstetric factors are important. Therefore, conducting early detection screening during pregnancy is encouraged to reduce postpartum haemorrhage maternal death.